Enhancing Employee Performance Through Lean Technical and Social Practices: A Case Study in Oil and Gas Laboratory Services - Muntaha, Cholip; Hendar (Yayasan Sinergi Kawula Muda, 2025)
This study examines the application of Lean Technical and Social Practices in enhancing employee performance within the oil and gas laboratory services sector. The oil and gas industry plays a crucial role in Indonesia's economy, yet it faces operational challenges due to fluctuating global oil prices and stringent regulations. The research investigates strategies for improving efficiency and productivity in the sector, with a focus on Total Quality Management (TQM), Just in Time (JIT), and Lean Social Practices. The problem addressed is the need for enhanced operational efficiency and labor productivity in oil and gas laboratory services. This paper fills the gap in research regarding the direct effects of TQM and JIT on employee performance in the oil and gas laboratory services context. While these practices have been widely studied in manufacturing, their impact on employee performance in this specific service sector remains underexploredA quantitative research approach was employed, using structured questionnaires to gather data from 77 participants involved in oil and gas laboratory services. The results show that while TQM significantly improves employee performance both directly and indirectly, JIT only yields positive outcomes when mediated by Lean Social Practices. The study advances the understanding of socio-technical integration by showing that combining technical and social practices delivers sustainable performance gains and practical management benefits in oil and gas laboratory services.